Pelatihan Pembuatan Bahan Ajar Digital Di SMK Swasta 2 Nurhasanah Medan - Saiful Anwar Matondang; Syahlan Syahlan; Mardiansyah Mardiansyah (STMIK Royal, 2023)
The rapid development of technology demands an increase in the competence of Human Resources. Utilization of Information Technology and Computers for Vocational High School level learning is very vital to enter the era of the industrial revolution 4.0. This activity helps schools prepare for the digitalized system process so that they can produce quality graduates who are able to compete globally by mastering technology. The purpose of this activity is to provide knowledge to teachers at Private Vocational School 2 Nurhasanah Medan regarding the manufacture of digital-based teaching materials and provide skills to teachers at Private Vocational School 2 Nurhasanah Medan in making digital teaching materials by utilizing the flipsnack application. The target audience for this activity was 20 teachers at SMK 2 Nurhasanah Medan. Two problems can be solved through ICT mastery workshops (training and mentoring). This training was held from August to November 2022. The results of the activity showed that the participation of the training participants showed satisfactory results where 90% of the participants had attended the training activities; all activities have met the set achievement targets, and The mentoring activities carried out have been able to improve the teacher's ability to compile and make teaching materials and materials for learning